2014
DOI: 10.2139/ssrn.2378884
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Within-Sector, Upstream and Downstream Energy Taxes on Innovation and Productivity

Abstract: The aim of the paper is to investigate the effect of environmental stringency on innovation and productivity using a cross-country panel made up of 7 European countries for 13 manufacturing sectors over the years [2001][2002][2003][2004][2005][2006][2007]. This research topic goes under the heading of Porter Hypothesis (PH) of which different versions have been tested. We take into consideration both the strong and the weak versions while adding some peculiarities to the analysis. Firstly, we assess the role p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Franco and Marin (2014) estimate the productivity effects of energy tax on manufacturing sectors in 7 European countries, accounting for spillovers for both within-sector, and upstream and downstream sectors. They find that the strongest effects on productivity come from taxes on downstream sectors, as they stimulate suppliers of heavy-regulated sectors to innovate more and increase energy efficiency.…”
Section: Industry Levelmentioning
confidence: 99%
“…Franco and Marin (2014) estimate the productivity effects of energy tax on manufacturing sectors in 7 European countries, accounting for spillovers for both within-sector, and upstream and downstream sectors. They find that the strongest effects on productivity come from taxes on downstream sectors, as they stimulate suppliers of heavy-regulated sectors to innovate more and increase energy efficiency.…”
Section: Industry Levelmentioning
confidence: 99%
“…Not accounting for the endogeneity of environmental policy proxies through an appropriate instrumental variable approach may bias estimates of environmental regulation effects on economic performance. 2 This drawback is also shared by Franco and Marin (2013), a very recent contribution that looks at both the impact on innovation and total factor productivity using energy tax intensity (energy tax revenues per unit of value added) as a proxy of environmental policy stringency. 3 2 Also in the related, large literature on the pollution heaven hypothesis that investigates the impact of environmental regulation on the relocation of manufacturing enterprises few papers account for endogeneity of environmental policy variables (Xing and Kolstad, 2002;Ederington and Minier, 2003;Levinson and Taylor, 2008).…”
Section: Related Literaturementioning
confidence: 99%
“…With respect to a country-level analysis we can better capture the effects of sector-specific environmental policies, on the one hand, and the dynamics of competition that takes place within a sector, on the other hand. The only other contribution addressing a similar research question is Franco and Marin (2013). We improve on their research by going a great lengths towards accounting for the endogeneity of the policy proxy we adopt in our empirical framework.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2011) proposed the relationship between productivity measured by Malmquist Luenberger index and environmental regulation and found more stringent enforcement of environmental regulation can help to promote the productivity [11]. Franco and Marin (2013) support the above conclusions by using energy taxes strength to proxy environmental regulation stringency in manufacturing [23]. suggested that local government may use environmental regulations to achieve economic objectives [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars believe that compensation effect can be achieved which can support porter hypothesis. Then the environmental quality can be greatly improved through effective environmental regulation (Berman and Bui, 2001; Yang et al, 2012; Franco and Marin, 2013; Peuckert, 2014; Yang et al, 2018) [21][22][23][24][25]. Zhang et al (2011) proposed the relationship between productivity measured by Malmquist Luenberger index and environmental regulation and found more stringent enforcement of environmental regulation can help to promote the productivity [11].…”
Section: Literature Reviewmentioning
confidence: 99%